2021
DOI: 10.3390/metabo11080562
|View full text |Cite
|
Sign up to set email alerts
|

2-Hydroxypropyl-β-cyclodextrin Regulates the Epithelial to Mesenchymal Transition in Breast Cancer Cells by Modulating Cholesterol Homeostasis and Endoplasmic Reticulum Stress

Abstract: Cholesterol metabolism affects endoplasmic reticulum (ER) stress and modulates epithelial-mesenchymal transition (EMT). Our previous study demonstrated that 2-hydroxypropyl-β-cyclodextrin (HP-β-CD) attenuated EMT by blocking the transforming growth factor (TGF)-β/Smad signaling pathway and activating ER stress in MDA-MB-231 cells. To further assess the detailed mechanisms between cholesterol metabolism, ER stress, and EMT, LXR-623 (an agonist of LXRα) and simvastatin were used to increase and decrease choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…A study conducted in 2017 indicated that in cholesterol-loaded cells, HPβCD had the potential to expand the active cholesterol pool, being the first study documenting that SREBP1 levels were reduced following HPβCD treatment [56]. Contrary to this, in MDA-MB-231 cells, a dose-dependent increase in the expression of HMGCR is reported, with reduced expression of cholesterol efflux proteins ABCA1 and ABCG1 following treatment with HPβCD [57]. This consequently necessitates further mechanistic investigations pertaining to exactly how HPβCD modifies the cellular cholesterol composition in various cancer cell types.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in 2017 indicated that in cholesterol-loaded cells, HPβCD had the potential to expand the active cholesterol pool, being the first study documenting that SREBP1 levels were reduced following HPβCD treatment [56]. Contrary to this, in MDA-MB-231 cells, a dose-dependent increase in the expression of HMGCR is reported, with reduced expression of cholesterol efflux proteins ABCA1 and ABCG1 following treatment with HPβCD [57]. This consequently necessitates further mechanistic investigations pertaining to exactly how HPβCD modifies the cellular cholesterol composition in various cancer cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our previous study indicated that the activating LXRα, which promoted cholesterol efflux by augmenting ABCA1 and ABCG1 expressions, could significantly reverse tunicamycin-induced ER stress in hepatocytes and macrophages [ 20 ]. Moreover, cholesterol homeostasis was also revealed to modulate the epithelial–mesenchymal transition (EMT) by regulating the ER stress in breast cancer cells [ 33 ]. Furthermore, in the occurrence of ED and cardiovascular disturbances, ER stress is a critical mechanism of ED [ 23 , 26 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol may be removed from the plasmatic membrane by MβCD, which results in increased cholesterol synthesis and the inhibition of ABCA1-mediated efflux [ 34 ]. Zhao et al also showed that treating MDA-MB-231 cancer cells with 2-hydroxypropyl-β-cyclodextrin leads to the upregulation of cholesterol synthesis and LDLR, as well as reduced ABCA1 expression [ 35 ]. Therefore, cyclodextrins exert similar effects as those observed with HA-atRA or HA-C18:1.…”
Section: Discussionmentioning
confidence: 99%